L'art contemporain depuis 1945. - Pradel, Jean-Louis (Paris : Bordas Paris, 1992)
Ando, Tadao ; Andre, Carl ; Arman ; Arroyo, Eduardo ; Bacon, Francis ; Balthus ; Baquié, Richard ; Barcelo, Miguel ; Baselitz, Georg ; Basquiat, Jean-Michel ; Beuys, Joseph ; Blais, Jean-Charles ; Boltanski, Christian ; Broodthaers, Marcel ; Calder, Alexander ; Caro, Anthony ; Cattani, Emmanuel ; César ; Chia, Sandro ; Chillida, Eduardo ; Combas, Robert ; Courmes, Alfred ; Cragg, Tony (Anthony) ; Dubuffet, Jean ; Errò ; Fabro, Luciano ; Filliou, Robert ; Fischl, Eric ; Riverhead (New York) ; Foster, Norman ; Garouste, Gérard ; Giacometti, Alberto ; Gilbert & George ; Haacke, Hans ; Hamilton, Richard ; Hanson, Duane ; Hockney, David ; Hucleux, Jean-Olivier ; Immendorff, Jörg ; Johns, Jasper ; Jorn, Asger ; Kabakov, Ilya ; Kersalé, Yann ; Kienholz, Edward ; Klein, Yves ; Kuramata, Shiro ; Lam, Wifredo ; Leger, Fernand ; Long, Richard ; de Maria, Walter ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Niemeyer, Oscar ; Nouvel, Jean ; Oldenburg, Claes ; Pagès, Bernard ; Paik, Nam June ; Parc, Julio Le ; Picasso, Pablo ; Pignon-Ernest, Ernest ; Polke, Sigmar ; Pollock, Jackson ; Rebeyrolle, Paul ; Rivers, Larry ; Ryman, Robert ; Saul, Peter ; Saura, Antonio ; Segal, George ; Serra, Richard ; Smith, David ; Smithson, Robert ; Solano, Susana ; Soto, Jesus Rafael ; Soulages, Pierre ; Stella, Frank ; Tingueley, Jean ; Twombly, Cy ; Vasarely, Victor ; Viallat, Claude ; Wall, Jeff ; Warhol, Andy
Chronologie p. 108-109
Frans
boek
Keywords: Duitsland; Frankrijk; Italië; New York; Spanje